2016
DOI: 10.1002/tesq.272
|View full text |Cite
|
Sign up to set email alerts
|

Native and Nonnative Teachers of L2 Pronunciation: Effects on Learner Performance

Abstract: Both native and nonnative language teachers often find pronunciation a difficult skill to teach because of inadequate training or uncertainty about the effectiveness of instruction. But nonnative language teachers may also see themselves as inadequate models for pronunciation, leading to increased uncertainty about whether they should teach pronunciation (Golombek & Jordan, 2005). Although studies have regularly shown that instruction is effective in promoting pronunciation improvement (Saito, 2012), it is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 73 publications
12
78
2
Order By: Relevance
“…The participants neither received a significant overall improvement in their comprehensibility or accentedness in both the NST and the NNST's class. The discrepancy between the finding in Levis et al (2016) and the present study may be attributed to the differences of the teaching classes. In Levis et al (2016), the students in the NST and the NNST's class experienced almost the same teaching procedure, teaching materials, classroom activities, etc.…”
Section: Testing Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…The participants neither received a significant overall improvement in their comprehensibility or accentedness in both the NST and the NNST's class. The discrepancy between the finding in Levis et al (2016) and the present study may be attributed to the differences of the teaching classes. In Levis et al (2016), the students in the NST and the NNST's class experienced almost the same teaching procedure, teaching materials, classroom activities, etc.…”
Section: Testing Resultscontrasting
confidence: 99%
“…Levis et al (2016), for instance, found that the elt.ccsenet.org English Language Teaching Vol. 9, No.…”
Section: Testing Resultsmentioning
confidence: 99%
See 3 more Smart Citations